2008
DOI: 10.1073/pnas.0707736105
|View full text |Cite
|
Sign up to set email alerts
|

The enzyme mechanism of nitrite reductase studied at single-molecule level

Abstract: A generic method is described for the fluorescence ''readout'' of the activity of single redox enzyme molecules based on Fö rster resonance energy transfer from a fluorescent label to the enzyme cofactor. The method is applied to the study of copper-containing nitrite reductase from Alcaligenes faecalis S-6 immobilized on a glass surface. The parameters extracted from the single-molecule fluorescence time traces can be connected to and agree with the macroscopic ensemble averaged kinetic constants. The rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
85
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 44 publications
(54 reference statements)
3
85
0
Order By: Relevance
“…2 but at the moment is not required to explain the observed behavior. Molecule-to-molecule variability has begun to be quantified in immobilized NiR molecules (24,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 but at the moment is not required to explain the observed behavior. Molecule-to-molecule variability has begun to be quantified in immobilized NiR molecules (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…This spectral change was recently employed to make a proximal dye molecule a fluorescent reporter of the T1 Cu oxidation state (24). The oxidized Cu significantly quenches the dye fluorescence via Förster resonant energy transfer (FRET) due to overlap between the dye's emission and the colored Cu's absorption, whereas the reduced colorless Cu leaves the dye unquenched and maximally emissive (24), Fig. 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to changes in the redox potentials and thus in the driving force of the ET reaction, several structural changes in the redox centers have been reported as a result of substrate binding, which may also influence the inter-copper ET rate by changing the reorganization energy (16,25,30,31). These rearrangements include subtle changes in the Cys-His bridge linking T1-and T2Cu (32) and conformational transitions of the catalytically relevant active site residue Asp-92 (see below and Ref.…”
mentioning
confidence: 99%
“…Studies have shown that completing the experiment within turnover conditions may also ensure that photobleaching does not affect the accuracy of the experimental findings. 49 …”
Section: Single-molecule Experimentsmentioning
confidence: 97%